Boosting the Photocatalytic Activity of P25 for Carbon Dioxide Reduction by using a Surface‐Alkalinized Titanium Carbide MXene as Cocatalyst - Ye, Minheng; Wang, Xin; Liu, Enzuo; Ye, Jinhua; Wang, Defa (ChemSusChem, 2018)
Although they are widely used as cocatalysts in promoting photocatalysis, practical application of noble metals is limited by their high cost and rarity. Development of noble‐metal‐free cocatalysts is thus highly demanded. Herein titanium carbide (Ti3C2) MXene is shown to be a highly efficient noble‐metal‐free cocatalyst with commercial titania (P25) for photocatalytic CO2 reduction. Surface alkalinization of Ti3C2 dramatically enhances the activity; the evolution rates of CO (11.74 μmol g−1 h−1) and CH4 (16.61 μmol g−1 h−1) are 3‐ and 277‐times higher than those of bare P25, respectively. The significantly enhanced activity is attributed to the superior electrical conductivity and charge‐carrier separation ability, as well as the abundant CO2 adsorption and activation sites of surface‐alkalinized Ti3C2 MXene, indicating its promise as a highly‐active noble‐metal‐free cocatalysts for photocatalytic CO2 reduction. Ti3C2 MXene is used as a cocatalyst to boost the photocatalytic activity of titania (P25) for CO2 reduction into hydrocarbon solar fuels. Surface alkalinization of Ti3C2 dramatically enhances the activity and, especially, the selectivity for CH4 evolution. The high intrinsic electrical conductivity and strong CO2 adsorption/activation capability of this MXene could account for its enhanced photocatalytic activity.